The Views Of John Burton On The Qur’ânic History In The Context Of His Work The Collection Of The Qur’ân - Mete, Şeyma; Saylan, Nesrişah (Fırat University, 2022)
This study was prepared to evaluate the English orientalist John Burton’s views based on his book The Collection of The Qur’a?n. Burton was a prominent figure known for his works on the history of the Qur’a?n, in the context of the Qur’a?nic history in particular, and his efforts to explore the nature of the comments which included the process of the development of the Qur’a?nic texts and its far-reaching history after the Prophet Mohammad (pbuh). In contrast to the other orientalists, Burton had a different approach in some topics. From time to time, he criticized other orientalists and tried to connect the issue of jam al-Qur’a?n with the naskh (abrogation) and attended to seperate Qur’a?n and Mushaf concepts in a sharp contrast. This study basicly aims to examine and explain John Burton’s opinions about the history of the Qur’a?n, in other words, the issues related to the textualization and the authenticity of the Qur’a?n.

Bu çalışma Kur’ân Tarihi araştırmalarıyla öne çıkan İngiliz Oryantalist John Burton (1929-2014)’un “Kur’ân’ın Cem’i" adlı eserinin Kur’ân tarihi bağlamında değerlendirilip, özellikle Hz. Peygamber’den (s.a.v.) sonra Kur’ân’ın metinleşme sürecinin şümûllu tarihini ihtiva eden görüşlerinin mahiyetini tespit amacıyla ortaya konmuştur. Burton’un diğer oryantalistlerin aksine bazı konularda farklı bir tutum içerisinde olduğu görülmüştür. Burton, “Kur’ân’ın Cem’i” adlı eserinde Kur’ân’ın tedvini meselesini nesih konusuyla irtibatlandırmaya çalışmıştır. Bu konuda diğer oryantalistlerin nesih olgusunu gereği gibi kavrayamadıklarından ötürü yanlış sonuçlara ulaştıklarını ifade edip onları eleştirmiştir. Ayrıca Burton, Kur’ân ve Mushaf kavramları arasında keskin bir ayrıma gitmiştir. Bu bağlamda Burton diğer Oryantalistleri İslâmî rivâyetleri herhangi bir eleştiri metodundan geçirmeden kabul etme konusunda da eleştirmiştir. Bu konulara ek olarak Burton’un yedi harf meselesi ve kırâatler hakkında öne sürdüğü görüşler izah edilip incelenmiştir.
The Collection of the Qur'ân Özelinde John Burton'un Kur'ân Tarihi'ne Bakışı
Keywords: Religious Studies; Din Araştırmaları